HISTORICAL-WORLD OUTLOOK BASES OF FUNCTIONAL-PLANNING STRUCTURE OF THE AHMED YASAWI MAUZOLEUM - Mamasharipova G. A.; Taubayeva M. E.; Nurbetova G. O.; Dzhapparova R. T.; Rakhimzhan K. A.; Issayev M. S.; Giritlioglu M. (Scientific Journal of Pedagogy and Economics, 2019)
The Mausoleum of Khoja Ahmed Yasawi is located in the city of Turkestan, Kazakhstan. The mausoleum is a vivid example of medieval monuments, and it was built over the grave of the Turkic poet and Sufi preacher Ahmed Yasawi at the end of the 14th century by the order of Emir Timur. To date, many researchers have put forward different ideas about the mausoleum. The plan, functions of the premises, ornament and the decoration of the structure show the characteristics of the Sufi tariqa of Yasawiya, based on the traditional Turkic worldview. This article will examine the historical and philosophical foundations and functional purpose of the plan and architecture, and as the order of location of the mausoleum’s premises. In addition, an analysis of insufficiently researched functions and names of the building’s premises, as well as their continuity from the point of view of the pre-Islamic religious beliefs of the Central Asian peoples and the concept of Islam is conducted. Evidence is provided.